Pertussis Toxin Ameliorates Microglial Activation Associated With Ischemic Stroke - Zhou, Feihui; Liu, Rong; Han, Pengcheng; Zhang, Xingkui; Li, Zhigao; Zhang, Shen; Liu, Chang; Xia, Yang; Tang, Zhiwei (Frontiers in Cellular Neuroscience, 2020)
Objective: To investigate the effect and the underlying mechanism of Pertussis toxin (PTX) on microglia in the setting of cerebral ischemia. Methods: We tested the effect of PTX 400 ng/days on middle cerebral artery occlusion stroke model by evaluating the neurologic function, infarct size, microglial distribution, and activation. In parallel, we also tested the effect of PTX on primary cultured microglia by evaluating microglial proliferation, activation, cytokine release, and CX3CR1 expression. Results: PTX reduced the poststroke infarct size, improved the neurologic function as evaluated by Longa score, and reduced microglial aggregation and activation in the infarcted area. Further, PTX significantly decreased lipopolysaccharide-stimulated microglial proliferation, the release of interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α), and the expression of CX3CR1. Interpretation: PTX treatment in stroke reduced microglial accumulation and activation in the infarct zone, resulting in a better functional outcome. The benefits of PTX treatment may be attributed to the reduced production of proinflammatory cytokine such as IL-1β and TNF-α and reduced expression of chemokine CX3CR1.